PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR IPAS MATERI TEKNOLOGI UNTUK KEHIDUPAN DI KELAS V SDN 2 PALANGKA - Amianto, Runi; Natalina, Kristina; Fransiska, Carolina (Sangkalemo : The Elementary School Teacher Education Journal, 2025)
This research is a quantitative research using an experimental research type, by testing the differences between groups using the Problem Based Learning learning model, with groups using conventional models. This research design is a non-equivalent control group design, by conducting an initial test before being treated and after being treated to measure students' cognitive abilities. The teaching actors in this study were teachers in the control group and students in the experimental group. The average value of the pre-test experiment was 59.9 and the average control was 58.42 and the average value of the post-test experiment was 82.5 and the average control was 76.84 with the difference in the average pre-test and post-test experiment being 22.6 and the control was 18.42. There was a significant increase in the average pre-test results with the average post-test results. Based on the paired Sample T-Test test, the Sig.2-tailed result was 0.001, this value is smaller than 0.05, so Ha is accepted and Ho is rejected. Meanwhile, when comparing the t-count value with the t-table, there is a t-count value of 7,032> 1,682 from the t-table value, so Ha is accepted and Ho is rejected. So it can be concluded that there is an influence of the use of the problem based learning model on the learning outcomes of science science material on technology for life in class V SDN 2 Palangka.